Message from the Editor-in-Chief - Martins, Lina (Canadian Journal of Wound, Ostomy and Continence, 2025)
"Autumn shows us how beautiful change can be" - Unknown In this second issue of our newly branded, peer-reviewed Canadian Journal of Wound, Ostomy and Continence (CJWOC), we continue to change and grow our publication in response to your feedback requesting more evidence to support the work within our tri-specialty. Immerse yourself in evidence synthesis as you read the scoping review and systematic review within the pages of this issue. The scoping review authored by Mosa, Jilek, Su, Ketchmark, Ammar, and Kennedy aims to map out and explore the existing literature on pressure injury wound healing with vitamin C supplementation, identifying gaps and key concepts. Ostomy care is known by many as the foundation of our specialty. It is exciting for us to see researchers and authors delve further into this aspect of our tri-specialty in order to better under-stand the available evidence and gaps that need addressing. The must-read article authored by Hutton, Prins, Yuan, Solitano, Radford, Vuyyuru, Abushamma, Rieder, and Jairath on behalf of the EndO-trial Consortium is a systematic review that comprehensively identifies, evaluates and synthesizes relevant studies and critically appraises the quality of nursing guidelines for ostomy care. Our first Guest Editorial by John Gregory, gives us a snapshot of Nurses Specialized in Wound, Ostomy and Continence Canada (NSWOCC) 44 th Annual Conference. This editorial emphasizes the importance of extending our focus beyond the traditional study of etiologies, products, and technologies within our tri-specialty. Aligning with the conference planners’ objectives, it encourages us to critically examine our own biases and to strive for the delivery of truly individualized and holistic patient care. We challenge each and every one of our NSWOC and SWAN colleagues and health care partners to contribute to the change and growth to our association’s official publication, CJWOC. Please contact us with your publication proposals; your insights and contributions are valued.